A striking new genus and species of troglobitic Campodeidae (Diplura) from Central Asia - Alberto Sendra; Boris Sket; Pavel Stoev (Subterranean Biology, 2017)
A striking new genus and species of Campodeidae (Diplura), Turkmenocampa mirabilis Sendra & Stoev, gen.n., sp.n., found in Kaptarhana cave in Eastern Turkmenistan is described. This represents the first record of Diplura from Central Asia and also the first terrestrial troglobiont found in Turkmenistan. The new taxon shows several unique characters such as the lack of crests on the telotarsus, the presence of a side-shoot process and the shape of barbs on the ventral side of the laminar telotarsal processes hitherto unknown in other members of this family. Although T. mirabilis is tentatively placed in the subfamily Plusiocampinae, its true affinities remain uncertain. The new finding provides further support to the importance of Kaptarhana as a refuge for a number of endemic invertebrates.